Aluminum Castings of High Strength - Robert S. Archer (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1927)
THE proper material of construction for a given purpose is that material which meets the requirements satisfactorily at the lowest ultirnatc cost. It is consistent with this principle that most aluminum castings are made of an alloy containing about 8 per cent. copper. This alloy possesses mechanical properties satisfactory for general engineering purposes together with manufacturing characteristics leading to the production of finished castings at low cost. It is to the aluminum industry what gray iron is to the iron and steel industry. Just as some services require "semi-steel," malleable castings or steel castings instead of gray iron, there is a certain and growing demand for aluminum castings of superior strength or ductility, or both. Since the beginning of .the industry producers and others have sought to develop alloys or processes by which such castings could be made. Out of these efforts have emerged many alloy compositions and special processes, of which only a few have had sufficient merit to survive. It is the purpose of this paper to describe those which seem to the authors to offer the greatest promise for the production on a commercial scale of aluminum castings of superior mechanical properties, with special reference to heat-treated castings. The suitability of an alloy or process for actual manufacture is affected by so many factors that the problem of appraisal is not a simple one. Since this is such an important part of the whole subject it is proposed to discuss briefly some of the requirements. The final verdict is of course the result of commercial trial and experience. It will therefore, perhaps, be profitable to employ a somewhat historical method of treatment in discussing the subject of alloy development. The alloys or processes to be used in the production of aluminum castings are to be considered from the standpoint of their effects on both the utility and the cost of the finished casting. Specific gravity and mechanical properties come under the first head, while the properties